Degrade to survive : the intricate world of piroplasmid proteases - Florin-Christensen, Mónica (2023)
Piroplasmids of the genera Babesia, Theileria, and Cytauxzoon are tick-transmitted parasites with a high impact on animals and humans. They have complex life cycles in their definitive arthropod and intermediate vertebrate hosts involving numerous processes, including invasion of, and egress from, host cells, parasite growth, transformation, and migration. Like other parasitic protozoa, piroplasmids are equipped with different types of protease to fulfill many of such essential processes. Blockade of some key proteases, using inhibitors or antibodies, hinders piroplasmid growth, highlighting their potential usefulness in drug therapies and vaccine development. A better understanding of the functional significance of these enzymes will contribute to the development of improved control measures for the devastating animal and human diseases caused by these pathogens.